Subjective Health Status and Immigration: Evidence across Europe - Karamanis, Dimitrios; Xesfingi, Sofia; Kechrinioti , Alexandra (SPOUDAI Journal of Economics and Business, 2020)
Subjective health status and migration are critical issues in healthcare policy. There are many health challenges to resolve and at the same time, migration has reached to historic highs, leading to different views among immigrants and natives, and policy makers. Our research focuses on the subjective health status reported by European habitants, on its differentiation with respect to participants’ origin, and on whether various demographic, macroeconomic and other factors, affect it. Using survey data of 227,200 respondents from 22 countries and over the period 2002-2016, and employing logit estimation techniques, we analysed the effect of demographic, macroeconomic and other factors in shaping respondents’ subjective health status. Our results demonstrate the important role of all demographic factors. Immigrants report a higher subjective health status, while macroeconomic conditions and foreign presence in a country do play an important role. A country’s healthcare provision state and health expenditures can moderate the negative effect of foreigners’ presence and thus the reported health status of natives. The factors influencing subjective health status are complex and interdependent. However, government policies should increase social cohesion, since the latter is not only related to health care outcomes but also can be a tool for disseminating social inequalities. Keywords: JEL: F22; I10; O52